Peran Ilmu Kimia dalam Kehidupan Sehari-hari Menurut Perspektif Santri Puteri Pondok Pesantren Al-Ihsan Banjarmasin - Gusti Hadiatus Solehah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to explore the role of chemistry in daily life from the perspective of female students (santri puteri) at Al-Ihsan Islamic Boarding School in Banjarmasin. Through qualitative methods including interviews and observations, this study investigates the understanding, perceptions, and experiences of the students regarding the practical applications of chemistry in their everyday lives. The findings highlight the significance of integrating chemistry education with real-life contexts to enhance students' comprehension and appreciation of this scientific discipline. Understanding the perspectives of female students in Islamic boarding schools sheds light on how chemistry education can be tailored to meet the needs and interests of diverse learner populations.